The Impact of Climate Change on Ponicum Production and Its Mitigation Strategies - Salih Ali Mohamed Bracaw (Journal of Scientific and Human Dimensions, 2026)
This study aims to investigate the impact of climate change on the productivity of Panicum grass (Panicum maximum) as a forage crop in Libya, in light of the accelerating global rise in temperatures, fluctuations in rainfall patterns, and the increasing frequency of drought events. The study adopted a descriptive–analytical approach, relying on climatic and agricultural data, international reports, and local field experience in cultivating Panicum grass in southern Libya The results showed that climate change has a direct impact on the growth and productivity of Panicum maximum, particularly during periods of heat stress and water scarcity, despite the crop’s relatively high tolerance compared to other forage crops. The study also indicated that increased atmospheric carbon dioxide concentrations may contribute to improving photosynthetic efficiency, partially mitigating the negative effects of climate change The study concludes that adopting climate-adaptive agricultural strategies is essential, including the use of modern irrigation techniques, improving soil fertility, and selecting heat- and drought-tolerant varieties. These measures contribute to enhancing the sustainability of forage production and achieving food security under rapidly changing climatic conditions.